HORMESIS PHENOMENA OF SOME PARAMETER ASPECT IN USAGE OF WATER LETTUCE (Pistia stratiotes L.) FOR PHYTOREMEDIATION PROCESS OF PETROLEUM LIQUID WASTE - Marisa, Hanifa; Estuningsih, Sri Pertiwi (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2017)
The research about potential test of water lettuce (Pistia stratiotes) in order of phytoremediation of petroleum liquid waste had been done during June untill December 2012 at Microbiology Laboratory, Department of Biology, Faculty of Science, The University of Sriwijaya, Indonesia. Completely Randomized Design was used in the experiment while the concentration of liquid waste as treatment were: 0, 15, 30, 45, 60 and 75 %. Each treatment were replicated 4 times. Three parameter was measured; Total Petroleum Hydrocarbons (TPH) reduction percentage, efficiency of phytoremediation and number of tillers. Regression analisys were used for the data and two of parameters show the hormesis phenomena, were; efficency of phytoremediation and number of tillers. The highestÂ peak effect of treatment for efficiency of phytoremediation and number of tillers was on 45 %. TPH reduction percentage was the only one parameter that shows linier regressionÂ Keywords hormesis, Pistia stratiotes, TPH, phytoremediation, tiller